Analisis Kualitas Sinyal terhadap Performa Intra dan Inter Handover pada Jaringan 4G LTE menggunakan Metode SSV - Ainun Nisyah; Aisah Aisah; Lis Diana Mustafa (Jurnal Jaringan Telekomunikasi, 2020)
One of the advantages of mobile communication is Handover. The research data can be used to identify network problems such as weak signal level (RxLev), poor signal quality (Rx Qual), etc. which cause the handover quality at that site in certain areas to be affected as well. The purpose of this research is to determine the quality of a signal that will affect the performance of the handover frequency both intra-frequency handover and inter-frequency handover on the 4G LTE network by paying attention to the KPI Site of the relevant vendor, in this case PT.GCI Indonesia. The method used to determine the signal quality and network performance in an area, namely measuring and retrieving data with a drive test. One of the data collection techniques on the 4G network is to use the SSV (Single Site Verification) method on the drive test so that the signal quality and handover analysis are known both intra handover and inter handover using the GENEX Probe software. From the results of this study, it was found that the signal quality and handover quality of the 4G LTE network met the standardization given by the KPI, for the requirements for the success of the handover, which was 100% with the signal quality of the RSRP and SINR parameters resulting in a percentage of 73% and 91.21% according to the standards desired by the operator. and vendors using the Single Site Verification (SSV) drive test method.